ChemInform Abstract: A Direct Metal‐Free Decarboxylative Sulfono Functionalization (DSF) of Cinnamic Acids to α, β‐Unsaturated Phenyl Sulfones. Issue 41 (October 2015) - Singh, Rahul; Allam, Bharat Kumar; Singh, Neetu; Kumari, Kumkum; Singh, Satish Kumar; Singh, Krishna Nand
Abstract A highly efficient decarboxylative synthesis of vinyl or alkynyl sulfones is achieved from cinnamic acids or propiolic acid derivatives and sulfonylhydrazides under mild reaction conditions.